The genus Isoetes L. (Isoetaceae, Lycophyta) in South-Western Asia [Güneybatı Asya'daki Isoetes L. (Isoetaceae, Lycophyta) cinsi] - (:unkn) unknown (Turkiye Klinikleri, 2008)
Quillworts or Çim Eǧreltisi, species of the genus Isoetes L. in Turkey and the Levant, are poorly studied despite extensive floristic studies in the region. The Flora of Turkey lists 4 taxa: Isoetes olympica A.Braun (2n = 22), I. histrix Bory var. histrix (2n = 20), I. subinermis (Bory) Cesca & Peruzzi [=I. histrix Bory var. subinermis Durieu (2n = 22)] and I. duriei Bory (2n = ca. 121). An additional species, I. anatolica Prada & Rolleri, was described in 2005 from Bolu province, and we report the first count for this species, 2n = 22. In Syria and Lebanon 2 species are known: I. olympica from a site in Syria and a known but undescribed plant from Akkar province (Lebanon) and adjacent Syria (2n = 22, first count). A preliminary molecular phylogeny for these species is presented; their distribution and cytology are discussed. The taxonomy and nomenclature of the I. histrix and I. duriei groups need considerable further study. The first hybrids for the region are documented. © TÜBİTAK.
Keywords: Chromosome counts; Çim eǧreltisi; Lebanon; Megaspores; Molecular phylogeny; Quillworts; Syria; Turkey